Hybrid Brillouin/Erbium fibre laser operating at long wavelength band - Harun, Sulaiman Wadi; Tamchek, M.; Abd-Rahman, M. Kamil; Ahmad, Harith (John Wiley & Sons, 2002)
The operation of the hybrid Brillouin/Erbium fibre laser (BEFL) in the long wavelength band (L-band) region is experimentally demonstrated. It uses a 50-m long erbium-doped fibre (EDF) with 400 ppm ion concentration as a gain medium to amplify the Stokes frequency signal generated in single mode fibre (SMF). The stokes frequency is shifted 10 GHz from the Brillouin pump with a tunability from 1598-1612 nm. The BEFL has the potential to be used in future wavelength division multiplexing (WDM) communication systems.